Untraceable Authentication Protocol for IEEE802.11s Standard - Abouhogail, Reham Abdellatif (International Journal of Communication Networks and Information Security (IJCNIS), 2022)
In the current paper, a new handover authentication protocol for IEEE802.11s Wireless mesh networks is presented. The new protocol divides the network into a number of cells, each cell contains a number of access points and based on the concept of ticket authentication, the mesh user takes a new ticket when enters the region of a new cell which decreases the handover latency. Moreover, in the current paper, a new idea for ticket generation is proposed, called Chain Ticket Derivation Function (CTDF), which uses the concept of a chain. Using CTDF in our proposed protocol raises the level of privacy for the users. The security analysis presented in the paper showed more strengths in our proposed scheme. Two formal verification tools, AVISPA and BAN logic are used to test the proposed protocol.